Teaching Vocabulary through Total Physical Response to Elementary Students - Deni Setiawan; Diani Nurhajati; Sulistyani Sulistyani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Vocabulary is an important language component to be learned by English language learners. It should be taught since early age, especially to elementary students. Teaching English vocabulary, especially to elementary students, required effective and interesting method that suits with children’s learning characteristics. Children understand something through what they see, listen, and do. Therefore, English teachers should select the suitable method that is child-friendly. One of the ways to teach vocabulary is through Total Physical Response (TPR) method. This study was descriptive qualitative research to describe teaching material, teacher’s roles and teaching stage in the implementation of TPR to teach vocabulary to elementary students The subject of this study was the English teacher who taught the elementary students. The data were obtained from observation during the teaching and learning process, interview to the subjects and document analysis. The findings revealed that the teaching material used by the teacher was correlated and suited with the students’ daily life. The teacher has several roles, namely as a planner, a director, a model, and an assessor. The stages of teaching vocabulary were pre-teaching, whilst-teaching and post-teaching. The teacher used varied classroom activities such as singing, listen and do, game and dialog. In the end, the teacher conducted a test to measure the students’ comprehension.